Arqueología del paisaje de las ocupaciones precolombinas de Guano: Patrones de asentamientos y lugares persistentes. - López Samaniego, Ana Carolina (2024)
The Guano canton, located in the province of Chimborazo, Ecuador, is home to a rich archaeological heritage that evidences the presence of several pre-Columbian cultures. This study aims to identify the landscape characteristics of Guano in relation to pre-Columbian human occupations, define the settlement patterns of these cultures and generate an occupational model that can be correlated with other cultural areas. Methodology: A mixed type of research was carried out, combining bibliographic survey with field work. Documentary sources, chronicles and previous archaeological studies were consulted to understand the historical and cultural context of the region. In addition, field visits were made to the archaeological sites identified, recording information on their location, physical characteristics and materials found. Results: The bibliographic analysis identified the landscape characteristics of Guano as an inter-Andean valley with an average altitude of 3,200 meters above sea level, characterized by its temperate climate and fertile soil.From the analysis of the data, an occupational model was generated that describes the spatial distribution of the archaeological sites in relation to the geographic characteristics of the territory. This model evidences a planned spatial organization by pre-Columbian cultures, who took maximum advantage of the available natural resources. Conclusions: The study made it possible to identify the landscape characteristics of Guano as a determining factor in the settlement pattern of the pre-Columbian cultures. The climatic conditions, the fertility of the soil and the diversity of ecological levels made this area an attractive space for the development of agricultural, livestock and commercial activities.